Émile Durkheim (1858-1917) - Tapia Alberdi, Fernando (Tendencias Sociales. Revista de Sociología, 2018)
A pesar de que los estudios sobre el pensamiento de Durkheim son numerosísimos, resulta sorprendente el escaso número de trabajos que se han ocupado de su itinerario vital e intelectual. Ello pone de manifiesto que, en el ámbito de los estudios durkheimianos, los especialistas han preferido la interpretación teórica de la obra al análisis sociobiográfico del autor. En este escrito presentamos una biografía del fundador de la escuela sociológica francesa, que explora los hitos fundamentales de su itinerario vital y científico-intelectual. Although the number of studies on Durkheim’s thought is very large, the scarcity of works focusing on his life and intellectual trajectory is surprising. This shows that, in the field of Durkheimian studies, specialists have preferred a theoretical interpretation of the work over socio-biographical analyses about the author. This paper provides a biography of the founder of the French school of sociology, one that explores the fundamental milestones in his life and scientific-intellectual itinerary.